An Optimized Player Taxonomy Model for Mobile MMORPGs with Millions of Users. (29th December 2011) - You, Fang; Liu, Jianping; Guan, Xinjian; Wang, Jianmin; Zheng, Zibin; Tam, Peter
Abstract : Massively multiplayer online role-playing games (MMORPGs) have great potential as sites for research within the social and human-computer interaction. In the MMORPGs, a stability player taxonomy model is very important for game design. It helps to balance different types of players and improve business strategy of the game. The players in mobile MMORPGs are also connected with social networks; many studies only use the player's own attributes statistics or questionnaire survey method to predict player taxonomy, so lots of social network relations' information will be lost. In this paper, by analyzing the impacts of player's social network, commercial operating data from mobile MMORPGs is used to establish our player taxonomy model (SN model). From the model results, social network-related information in mobile MMORPGs will be considered as important factors to pose this optimized player taxonomy model. As experimental results showed, compared with another player taxonomy model (RA model), our proposed player taxonomy model can achieve good results: classification is more stable.